(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The scientific study is devoted to the problems of administrative responsibility for violating the requirements of the by-laws of local self-government bodies. Legislative acts and the list of administrative offenses regulating the powers of local self-government bodies are studied. The article examines the works of scholars who have studied the peculiarities of administrative liability for violation of parking rules, ensuring silence in cities, and waste management.It is stated that the binding nature of decisions of local councils and their executive committees is one of the guarantees of local self-government. Guarantees of local self-government are defined as a system of conditions that provide territorial communities with the exercise of the right to local self-government. Attention is drawn to the fact that local councils make decisions on the budget, housing, communal services, land relations, improvement, education, and health care, and regulate other legal ties. Failure to comply with many by-laws of local self-government bodies may entail administrative liability. Administrative offenses in budgetary, land, environmental relations, and settlement improvement are analyzed. Cases of qualification of by-laws violations of local self-government as administrative misdemeanors are determined. The objective side of the composition of these administrative offenses is described. The authority of local self-government bodies to bring offenders to administrative responsibility is clarified. Proposals for expanding the competence of administrative commissions and executive committees in bringing administrative responsibility are made. It is proposed to establish a list of violations of by-laws of local self-government bodies in the Law of Ukraine On Local Self-Government in Ukraine, for which administrative responsibility is provided for citizens and legal entities.